SIFAT FISIKA DAN MEKANIKA PAPAN SEMEN PARTIKEL DARI LIMBAH KAYU ALAU (Dacrydium spp.) DENGAN BERBAGAI RASIO BAHAN BAKU DAN TINGKAT SUBSTITUSI GYPSUM (Physical and Mechanical Properties of Particle Cement of Dacrydium sp. Wood Waste With Different Raw Mate: Grace Siska1 , Sarinah1 , Gimson Luhan 1 Sinta Marito Sinaga2 - Administrator Journal (HUTAN TROPIKA, 2018)
ABSTRACTUsing round wood as a raw material of the product the less available day. Various efforts aremade to utilize wood as a raw material of a product, such as using waste from wood processingindustry. The purpose of this research is to know the quality of alau (Dacrydium spp.) woodparticle cement board and to know the effect of cement substitution with gypsum on the physicaland mechanical properties of alau particle board (Dacrydium spp.). Research design usedFactorial Random Design (RAL) factorial, with 2 factors pattern, namely factor A (cement ratio:particle) consist of 3 levels i.e. a1 (75% cement + 25% particle); a2 (80% cement + 20%particle); a3 (85% cement + 15% particle), factor B (gypsum substitution rate) consists of 2levels i.e. b1 (5%); b2 (10%). The research results indicate that the physical properties of density(with an average value of 1.47 g / cm3) and moisture content (?16%), and thickness development(17.47%) all meet the standards, whereas water absorption does not have value on JIS standard5414-1992. The result of testing of the mechanical properties of bending conformity (MoE)meets the standard, and the fracture conformity (MoR) that meets the test standard is 10%gypsum substitution (b2), while internal sticking (IB) there is no requirement of value in standardJIS A 5414-1992. Comparison of the ratio of raw materials and substitution of gypsumsignificantly influence the physical and mechanical properties of cement.Keywords: Particle cement board, physical characteristics and mechanics